Pandangan Falsifikasionisme tentang Keberadaan Tuhan dalam Pembelajaran Konsep Entropi - Sa’ban Fauzi, Ifan; Irawan; Hasanah, Aan (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
One of the learning objectives of science, especially in the last few curricula, is to gain belief in God Almighty based on the existence, beauty, and orderliness of His creation. But why do many scientists, especially natural science scientists, manifest themselves as a group that does not believe in the existence of God? The purpose of this study is to show how much connection there is between science and religion, especially to reveal how much real evidence shows the existence of God as the creator of the universe. The analytical tool used in this research is the falsification technique initiated by several philosophers, especially Karl Popper. The results of this research show strong evidence of the existence of God as the creator of the universe, which is doubted by many world scientists. The results of this research make it possible to open the barrier between science and religion, especially Islam.